Caries dental en niños de 2-18 años con enfermedades hematooncológicas. Hospital Manuel de Jesús Rivera, Managua, Nicaragua. Febrero- agosto 2011 - Espinoza-Palma, Alicia Samanta (Odovtos - International Journal of Dental Sciences, 2012)
Childhood cancer is becoming more frequent and it is a public health problem due the high rate of mortality and recurrence, although chemotherapy have improved substantially in recent years. This child population is susceptible to oral health problems such as cavities, dental extraction, and gingivitis, not for age related condition but also as a secondary effect of cancer treatment. Oral health in the cancer patient, under inmunosupression effects, takes a leading role in achieving progress and proper chemotherapy administration. Severe oral effects can compromise optimal treatment protocols and patient survival may be affected. The aim of the study was to identify present and past stages of dental caries, in addition to identifying the severity of caries in pediatric oncology patients. We performed a cross sectional study, 182 patients formed the sample at the Hematology-Oncology Service at Manuel Jesus Rivera Hospital, Managua, Nicaragua, during February to August 2011. The results show a DMF/T=7.37 teeth affected by dental caries, higher than the national average, for that age group. Severity of dental caries was categorized as Too Severe for permanent dentition on both sexes. We found a higher index DMF/T and dmf/t in patients receiving chemotherapy in combination with radiotherapy.